PERAN PEMERINTAH DESA BUNTULIA TENGAH MENGATASI PERILAKU MENYIMPANG MASYARAKAT: STUDI KASUS PENGANIAYAAN DUSUN CEMPAKA KABUPATEN POHUWATO KECAMATAN BUNTULIA PROVINSI GORONTALO - Dewinta Rizky R. Hatu; Sahrain Bumulo; Bilfadliyanto Bangga (Jurnal Ilmiah Sosiologi Agama (JISA), 2026)
This study examines how the village government performs its role in maintaining social order and addressing various forms of deviant behavior that emerge within the community. The research focuses on the efforts of the village administration in carrying out supervision, guidance, and social control to create a safe, orderly, and harmonious social environment. The purpose of this study is to describe and analyze the role of the village government in handling behavioral deviations and to identify the factors influencing the occurrence of social role deviations within society. This research employed a qualitative method with a descriptive approach. The research informants consisted of the village head, village officials, military officers (Babinsa), community leaders, religious leaders, and residents of Buntulia Tengah Village who were selected purposively. Data collection techniques included interviews, observations, and documentation, while data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings indicate that the village government has implemented supervisory, coaching, socialization, and collaborative measures with security authorities in overcoming deviant behavior, although the implementation still encounters various social obstacles and low levels of public awareness.